Een eeuw beeldende kunst in Limburg : 1900-2000 - Raskin, Ludo (Hasselt : Concentra, 2004)
Anten, Djef ; Ballewijns, Giljom ; Baltus, Georges M. ; Bamps, Paul ; Boedts, Jan ; Bronckaers, Oscar ; Coëme, Ri ; Damien, Jos. ; Douven, Jac. ; Geraets, Michel ; Guffens, Godfried ; Hendrix, Louis ; Hermans, Paul ; Jamine, Edmond ; Keelhoff, Frans ; [et al.]
Schenking Flanders DC
boek